Piezoelectric rod sensors for scour detection and vortex-induced vibration monitoring. (May 2022) - Funderburk, Morgan L; Park, Yujin; Netchaev, Anton; Loh, Kenneth J
As extreme events increase in frequency, flow-disrupting large-scale structures become ever more susceptible to collapse due to local scour effects. The objective of this study was to validate the functionality of passive, flow-excited scour sensors that can continue to operate during an extreme event. The scour sensors, or piezo-rods, feature continuous piezoelectric polymer strips embedded within and along the length of slender cylindrical rods, which could then be driven into the soil where scour is expected. When scour erodes away foundation material to reveal a portion of the piezo-rod, ambient fluid flow excitations would cause the piezoelectric element to output a voltage response corresponding to the dynamic bending strains of the sensor. The voltage response is dependent on both the structural dynamic properties of the sensor and the excitation fluid's velocity. By monitoring both shedding frequency and flow velocity, the exposed length of the piezo-rod (or scour depth) can be calculated. Two series of experimental tests were conducted in this work: (1) the piezo-rod was driven into sediment around a mock pier to collect scour data, and (2) the piezo-rod was used to monitor its own structural response by collecting vortex-shedding frequency data in response to varied flow velocities to establish a velocity–frequency relationship. The results showed that the piezo-rod successfully captured structural vortex-shedding frequency comparable to state-of-practice testing. A one-dimensional numerical model was developed using the velocity–frequency relationship to increase the accuracy of voltage-based length prediction of the piezo-rod. Two-dimensional flow modeling was also performed for predicting localized velocities within a complex flow field. These velocities, in conjunction with the velocity–frequency relationship, were used to greatly improve length-predictive capabilities.